DESAIN CETAKAN VACUUM FORMING UNTUK PEMBUATAN PLASTIC PACKAGING TRAY DI PT SM ENGINEERING - Wibisono, Bagus; Prakasa Hasibuan, Rizki (LPPM Universitas Putera Batam, 2022)
All manufacturing processes must begin with a design in the manufacture of products, including the thermoforming process. The thermoforming process has several stages in product design, namely: thermoforming product design and mold design. The mold is an illustration of the shape of the thermoforming product that will be made. The Vacuum Forming Department at PT SM Engineering received a request from customers to manufacture plastic packaging trays for cable sub-assembly products with part number NA100715R2-1. Based on this, the researcher intends to conduct research on product design and plastic packaging tray molds using the Design for Manufacture and Assemby (DFMA) method. Based on the DFMA analysis of the initial design, the components that make up the vacuum forming mold are 108 components with a weight of 23.95 kg, a total machining time of 22.16 hours and a total cost of Rp20,945,984. From the results of the initial design evaluation, a new design of vacuum forming molds was obtained. The new design designed was analyzed using DFMA and the results obtained that the components that make up the vacuum forming mold are 94 components with a weight of 23.05 kg, a total machining time of 18.91 hours and a total cost of Rp18.962.891. From the initial design and the newly designed vacuum forming design, after being compared based on the processing parameters, the best new design was selected.